2021
DOI: 10.1155/2021/6670135
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of Filipendula ulmaria Extract in Prevention of Prodepressant Effect and Cognitive Impairment Induced by Nanoparticles of Calcium Phosphates in Rats

Abstract: Mineral components of dental composites are used in many medical and dental applications, including preventive, restorative, and regenerative dentistry. To evaluate the behavioural alterations induced by nanosized particles of novel dental composites, by means of depressive level and cognitive functions, experimental groups of rats were chronically administered with nanosized hydroxyapatite (HA), tricalcium phosphate (TCP), and amorphous calcium phosphate (ACP) with or without simultaneous application of Filip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 54 publications
4
17
0
Order By: Relevance
“…The obvious beneficial role of antioxidant supplementation with FU extract on nano-CaP-induced hepatotoxicity cannot be compared to similar reports. However, although already known for its protective role by means of antioxidant and anti-inflammatory effects [ 24 ], the confirmation of benefits of using FU extract following nano-CaP administration could be found only in certain brain regions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The obvious beneficial role of antioxidant supplementation with FU extract on nano-CaP-induced hepatotoxicity cannot be compared to similar reports. However, although already known for its protective role by means of antioxidant and anti-inflammatory effects [ 24 ], the confirmation of benefits of using FU extract following nano-CaP administration could be found only in certain brain regions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mineral components of dental composites in nanoparticles were purchased from Sigma-Aldrich, Germany: hydroxyapatite nanopowder: <200 nm particle size (BET), ≥97%, and synthetic; tricalcium phosphate hydrate nanopowder: <200 nm particle size (BET); and calcium phosphate: amorphous nanopowder and <150 nm particle size (BET). The doses for nanosized calcium phosphates were determined to meet the following criteria, as previously described by Arsenijevic and coworkers [ 11 ]: to achieve the equimolarity, to level the lowest dose of calcium phosphates (HA) that showed toxic effects according to literature data [ 25 ] for experiments performed in vivo with nanosized particles, and to achieve the doses of calcium phosphates daily released from dental composites in vitro [ 26 ]. The route of administration ( per os ) was chosen to mimic the authentic way of application in humans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study demonstrated that the long term administration of hydroxyapatite or tricalcium phosphate nano particles had a significant prodepressant effect in rodents. Also, a prolonged treatment with amorphous calcium phosphate also resulted in a significant decline in cognitive functions, and these adverse effects were accompanied by the increased oxidative damage and apoptosis in the prefrontal cortex (52).…”
Section: Adverse Effects Of Bone Replacement Materialsmentioning
confidence: 99%